A new species of the Callophrys rubi (Linnaeus, 1758) group from Afghanistan (Lepidoptera, Lycaenidae). Issue 4 (2nd October 2022) - Krupitsky, Anatoly; Skrylnyk, Yuriy; Pak, Oleg
Abstract : A new species of the Callophrys rubi (Linnaeus, 1758) species group, C. hindukushica sp. n., is described from western extremities of the Hindu Kush range in central Afghanistan. The new species differs from the other members of the C. rubi group known from the Iranian Highland, namely C. naderii ten Hagen, 2008 from southeast Iran and C. rubi martinae ten Hagen, 2012 from northeast Iran and south Turkmenistan, in the light green colouration, greenish fringe lacking brown bordering, shape and size of the male androconia and details of the male and female genitalia. http://www.zoobank.org/urn:lsid:zoobank.org:pub:AB79DCE2-CEFE-4FDF-91F9-52EF46BA5CD2